Piloting a Methodology for Sustainability Education: Project Examples and Exploratory Action Research Highlights - Jensen, Cory; Kotaish, Mohamed; Chopra, Aditi; Jacob, Kiran A.; Widekar, Taqdees I.; Alam, Rahat (Emerging Science Journal, 2019)
This invited writing shares the education methodology known as Wicked problem, Experiences, Available Resources, Solution-Innovation (WEARS) and results from applying a pilot education program with a group of international students. The pilot involved three components that contribute to enhancing leadership skills based on stakeholder informed or bottom-up change: 1) developing a professional competition, 2) proposing a WEARS project, and 3) initiating a related outreach event. Outlines of student projects are shared. Students’ interests in generalized sustainability related education topics were polled and results are presented as an average of the group. Reflection on conducting the pilot is also presented from an exploratory action research perspective. Potential translation to higher education sustainability related projects was a driver for action research. Several conclusions are shared related to the educational structure and content for application of the WEARS methodology at a higher education institution. Future research and iterations of the program are proposed in coordination with a higher education institution that promotes interdisciplinary education. Specifically, means to select program candidates and longitudinal study of overall impacts are proposed as necessary to continuously update the WEARS methodology.